2012
DOI: 10.3945/jn.112.162628
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Quercetin Interact to Inhibit Neointimal Hyperplasia in Mice with a Carotid Injury

Abstract: Restenosis is a critical complication of angioplasty and stenting. Restenosis is multifactorial, involving endothelial injury, inflammation, platelet activation, and vascular smooth muscle cell (VSMC) proliferation. Thus, dietary strategies to prevent restenosis likely require the use of more than one agent. Resveratrol (R) and quercetin (Q) are polyphenols that are known to exhibit vascular protective effects. We tested whether R and Q administered in the diet interact to inhibit vessel stenosis in mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
1
25
2
1
Order By: Relevance
“…However, the levels of quercetin in red wine are typically ∼10-fold higher than the resveratrol levels. 36 In a recent study, Khandelwal et al showed that resveratrol and quercetin synergistically reduce the extent of restenosis (a complication of angioplasty and stenting), possibly by inhibiting vascular smooth muscle cell proliferation and inflammation. 36 Further, in a study by Zhou et al, transcriptomic and metabolomic profiling revealed synergistic effects of quercetin and resveratrol supplementation in high-fat diet-fed mice.…”
Section: Resveratrol and Quercetinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the levels of quercetin in red wine are typically ∼10-fold higher than the resveratrol levels. 36 In a recent study, Khandelwal et al showed that resveratrol and quercetin synergistically reduce the extent of restenosis (a complication of angioplasty and stenting), possibly by inhibiting vascular smooth muscle cell proliferation and inflammation. 36 Further, in a study by Zhou et al, transcriptomic and metabolomic profiling revealed synergistic effects of quercetin and resveratrol supplementation in high-fat diet-fed mice.…”
Section: Resveratrol and Quercetinmentioning
confidence: 99%
“…36 In a recent study, Khandelwal et al showed that resveratrol and quercetin synergistically reduce the extent of restenosis (a complication of angioplasty and stenting), possibly by inhibiting vascular smooth muscle cell proliferation and inflammation. 36 Further, in a study by Zhou et al, transcriptomic and metabolomic profiling revealed synergistic effects of quercetin and resveratrol supplementation in high-fat diet-fed mice. 37 It seems that additive/synergistic interactions between these two polyphenols may be one explanation for the French paradox, especially because both of these agents are present in red wine.…”
Section: Resveratrol and Quercetinmentioning
confidence: 99%
“…Despite the controversial results on the efficacy of RSV reported in 7 the literature, very recent data obtained in colon cancer cells have supported the notion that RSV, in spite of its low bioavailability, is able to act through its metabolites, mainly the sulpho-conjugate but also the combination of sulphate/glucuronide derivatives 15,16 . Despite the wide literature on RSV, only few preclinical studies have demonstrated the efficacy of RSV in an animal model or investigated the possibility of locally administering this antioxidant by eluting stents 6,7 . Based on our experience, we decided to set up a sterile, injectable, and hydrophilic RSV-containing compound (RSV-c).…”
Section: Introductionmentioning
confidence: 99%
“…There are several pioneering reports on RSV, including studies on the inhibition of the arachidonate metabolism via interactions with the 5-lipoxygenase and cyclooxygenase pathways in leukocytes [6][7][8][9][10][11][12] . However, RSV attracted little interest until 1979, when the "French Paradox" 13 reported the positive benefit of an RSV-containing diet, in particular the moderate consumption of red wine, for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that simultaneous use of quercetin and polyphenole can cause reduction of restinosis level (probably through inhibition of smooth muscle cell proliferation). Therefore, using a combination of quercetin and polyphenole has high potential in cancer control (41).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%